A web-based workplace exercise intervention among office workers with spinal pain: Protocol of a mixed methods study - Carlos Tersa-Miralles; Cristina Bravo; Filip Bellon; Maria Masbernat-Almenara; Francesc Rubí-Carnacea; Esther Rubinat Arnaldo (PLoS ONE, 2025)
Introduction Musculoskeletal disorders are a major cause of disability worldwide, significantly impacting office workers due to prolonged sitting and lack of movement. Implementing therapeutic exercise interventions in the workplace has been identified as a feasible and cost-effective strategy to address spinal pain. However, understanding workers’ perspectives and workplace barriers is essential for designing effective interventions. This study aims to develop and evaluate a web-based workplace intervention with active breaks to reduce spinal pain among office workers. Methods This study follows a sequential exploratory mixed-methods design. The qualitative phase will use semi-structured interviews with office workers to explore their experiences with spinal pain, active breaks, and perceived barriers to implementation. These findings will inform the development of a six-week web-based therapeutic exercise intervention, which will be evaluated through a two-arm cluster randomised controlled trial. The trial will compare an intervention group performing structured active breaks during work hours with a control group maintaining their usual routine. Primary outcomes include pain intensity (Visual Analogue Scale), spinal dysfunction (Spine Functional Index), and adherence to the program. Secondary outcomes include quality of life (EQ-5D-5L) and exercise motivation (Behavioural Regulation in Exercise Questionnaire-2). Statistical analyses will compare within- and between-group differences to assess the intervention’s effectiveness. Discussion Web-based interventions can enhance adherence to active breaks and provide an accessible, cost-effective solution for spinal pain management in sedentary workplaces. By adopting a mixed-methods approach, this study will generate valuable insights into implementing workplace exercise interventions, taking into account workers’ expectations, workplace context, and adherence factors. Findings may inform future interventions aimed at managing musculoskeletal disorders in office workers. Trial registration ClinicalTrials.gov NCT05571124